STRATEGIC PERSUASION: SECURING COMMUNITY SUPPORT FOR INTERNET INFRASTRUCTURE DEVELOPMENT - Putra, Gede Aldi Legawa; Leila Mona Ganiem, (Journal of Innovation Research and Knowledge, 2024)
The development of internet infrastructure is crucial for fostering economic and social progress in the digital age. However, obtaining approval from local communities for such projects can be challenging due to concerns about environmental impact and disruptions. This study analyzes the persuasive communication strategies employed by PT Linknet Tbk (First Media), an Internet Service Provider (ISP), to secure permits for infrastructure development. Using a qualitative case study approach, the research explores how different persuasive techniques were applied to engage communities and reduce resistance. Key strategies include the association technique, where the project is linked to long-term community benefits such as enhanced internet access; the integration technique, involving community participation and addressing concerns; the reward/pay-off technique, offering incentives; and the red herring technique, shifting focus from temporary disruptions to long-term gains. The findings show that these strategies effectively increased community support, streamlined the permit process, and minimized potential conflicts. The study concludes that persuasive communication is vital in building positive community relations and ensuring the successful implementation of infrastructure projects, particularly in regions where community approval is essential.